Antiangiogenic therapy with recombinant human endostatin may improve blood perfusion of cervical node with necrosis in nasopharyngeal carcinoma patients: a preliminary study by using contrast-enhanced ultrasound - Yang, Zhendong; Xiao, Huimin; Li, Xigui; Wei, Zhuxin; Kang, Min; Wang, Rensheng; Huang, Jianyuan (Frontiers in Oncology, 2025)
BackgroundThe cervical node with necrosis (CNN) is an important poor prognostic factor for nasopharyngeal carcinoma (NPC) patients. The tumor microenvironment of the CNN has severely insufficient blood perfusion, thus leading to hypoxia and reducing the effect of radiotherapy (RT) and chemotherapy. By using contrast-enhanced ultrasound (CEUS) as a monitoring method, we conducted this study to assess whether antiangiogenic therapy (AT) with recombinant human endostatin (RHES) may improve blood perfusion of the CNN.Materials and methodsFifteen NPC patients with CNN were enrolled and underwent CEUS the day before and day 5 after AT with RHES initiation, respectively. By analyzing the variations of CEUS parameters of CNN, such as peak intensity (PI), time to peak (TTP), and mean transit time (MTT) at different time points, we evaluate the impact of AT with RHES on blood perfusion of CNN.ResultsThe PI of day 5 after AT was significantly enhanced compared to the PI of the day before AT [−44.94 ± 4.72 (dB) vs. −50.33 ± 6.85 (dB), p < 0.001]. The TTP of day 5 after AT became dramatically shorter than the TTP of the day before AT [19.48 ± 3.63 (s) vs. 24.19 ± 6.93 (s), p = 0.031]. The MTT of day 5 after AT became obviously shorter than the MTT of the day before AT [28.08 ± 3.03 (s) vs. 33.76 ± 6.20 (s), p = 0.001].ConclusionThese results revealed that the blood volume and the blood flow velocity in the microvessels of the CNN increased after AT, indicating that AT with RHES may improve blood perfusion in the CNN of NPC, thus providing valuable insights for the clinical application of AT combined with RT and/or chemotherapy in NPC patients with CNN. Moreover, CEUS as a noninvasive and real-time monitoring method may be suitable for clinically evaluating tumor blood perfusion changes.